Versatile BP/Pd-FPEI-CpG nanocomposite for "three-in-one" multimodal tumor therapy. (October 2022) - Fu, Zhao; Ni, Dongqi; Cai, Shuangfei; Li, Haolin; Xiong, Youlin; Yang, Rong; Chen, Chunying
Abstract: Multimodal nanocatalytic therapy has shown promising potential in cancer treatments. However, to design an effective multimodal nanocatalytic modality, with a deep understanding of synergistic therapy, remains a grand challenge. Herein, we propose an innovative "three-in-one" multimodal strategy with integrated photothermal/photodynamic/chemodynamic modalities for tumor-specific treatment, by rationally constructing a multifunctional two-dimensional (2D) nanoplatform based on the black phosphorous (BP)/Pd nanosheets (NSs) via in-situ growth. Interestingly, such a hybridization of different types of 2D NSs mediates formation of the Pd-P coordination bonds. With strong interfacial Pd-P interaction, the heterostructured NSs display enhanced cascade enzymatic activities in tumor microenvironment, leading to sufficient generation of reactive oxygen species (ROS) as therapeutic species including cytotoxic superoxide (O2 − ) radicals by successive catalase-/oxidase-catalysis, and deleterious singlet oxygen ( 1 O2 ) radicals under light irradiation. The incorporation of Pd also improved the photothermal activity of the material. Furthermore, by facile functionalization with fluoro-polyethyleneimine (FPEI) and loading of cytosine-phosphate-guanine (CpG) as an immune adjuvant, the versatilities of this unique 2D hetero-nanoplatform are further extended, strikingly improving therapeutic efficacy for tumor cells, and simultaneously avoiding significant damage to normal tissues. The work provides useful insights into the design of new 2D nanoplatforms for multimodal tumor treatment. Graphical Abstract: A novel "three-in-one" multimodal strategy is developed for effective tumor-specific treatment, by integrating photothermal/photodynamic/chemodynamic modalities into a versatile two-dimensional nanotherapeutic platform, based on heterostructured black phosphorous/Pd nanosheets with strong Pd-P interaction. It provides new perspectives to design and construct multifunctional nanomedicines for tumor therapy. ga1 Highlights: Facile preparation of BP/Pd nanosheets with eco-friendliness under mild conditions. Superior cascade catalysis and improved photodynamic/photothermal effect by Pd-P interaction. Enhanced stability, biocompatibility and cell uptake by fluoro-polyethyleneimine. Increased TNF-α release of cells by loading of cytosine-phosphate-guanine. Excellent antitumor efficacy with good biosafety.